A RANDOMIZED‐CONTROLLED TRIAL OF AN INTERVENTION TO IMPROVE ANTIDEPRESSANT ADHERENCE AMONG LATINOS WITH DEPRESSION. Issue 7 (8th January 2013) - Interian, Alejandro; Lewis‐Fernández, Roberto; Gara, Michael A.; Escobar, Javier I.
<x xml:space="preserve">Abstract</x> Background Studies have consistently shown that Latinos with depression have lower adherence to antidepressant medication. Given that low adherence is associated with poorer response to treatment, this is a likely source of unequal care. The current study examined the efficacy of a motivational interviewing intervention for improving antidepressant adherence among Latinos with a depressive disorder. Methods Participants were 50 Latinos with a DSM‐IV diagnosis of major depression or dysthymia who were receiving treatment at a community mental health center. Participants were recruited from July 2007 to December 2009 and were randomized to receive usual care (UC) or Motivational Enhancement Therapy for Antidepressants (META). META participants received three sessions of motivational interviewing as an enhancement to their usual care. Participants were assessed as baseline (time 1), 5 weeks (time 2), and 5 months (time 3). Antidepressant adherence was measured with the Medication Event Monitoring System (MEMS®) and changes in depression were measured with the Beck Depression Inventory‐II (BDI‐II). Results After adjusting for covariates, META participants showed significantly higher antidepressant adherence than UC participants at time 2 (72% versus 42%, respectively, p < .01) and time 3 (60% versus 34%, p < .01). The groups did not differ on mean BDI‐II score across time. However, after adjusting for covariates, META participants were significantly more likely to show symptom remission on the BDI‐II, compared to UC participants (OR = 7.0, p < .05). Conclusions This initial trial of META demonstrated feasibility and promising effects for improving antidepressant adherence. Some effects on depression were also observed.